Conflictos, solidaridades y miradas en torno a la situación de calle : ciudad de Buenos Aires - Boy, Martín (El Colegio de México, 2014)
Usually, the experience of living in the streets is associated with homeless people but other groups inherently related are forgotten such as police, gangs, neighbors and etcetera. The aim of this paper is to characterize the relationships that exist between the different groups who are involved, directly or indirectly, in the dynamics of homelessness. Adults who live in the streets (ALS) were interviewed during the field work that finished with the writing of the phd thesis. In the network of relationships that is woven around homelessness is important to talk about the presence of the Big Other (the rest of society that does not sleep on the streets) and how the adults who live in the streets build closeness and intimacy while keeping distances with Big Other; sympathies and conflicts.